1999
DOI: 10.1097/00001648-199911000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Family Size, Infections, and Asthma Prevalence in New Zealand Children

Abstract: A mother's prepregnancy obesity has been suggested as a risk factor for having offspring with an abdominal wall defect. We evaluated this hypothesis among 104 cases of gastroschisis--a severe birth defect of the abdominal wall most prevalent in infants of young women--and 220 controls with no defect. Using Quetelet's index (QI = weight in kg/height in m2) as a measure of body mass, we found a higher risk of gastroschisis (odds ratio (OR) = 3.2; 95% confidence interval (CI) = 1.4-7.3) for underweight mothers (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 15 publications
4
48
2
Order By: Relevance
“…Our finding of an increased asthma risk for early transient wheezing with day care attendance agrees with the findings of several crosssectional studies (Nafstad et al 1999;Wickens et al 1999). Moreover, we observed that the risk of asthma is highest when children were sent to day care centers before 4 months of age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of an increased asthma risk for early transient wheezing with day care attendance agrees with the findings of several crosssectional studies (Nafstad et al 1999;Wickens et al 1999). Moreover, we observed that the risk of asthma is highest when children were sent to day care centers before 4 months of age.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of a protective role of sibship size on asthma is consistent with the results of many epidemiologic studies (Infante-Rivard et al 2001;Wickens et al 1999). Infections from older siblings during early life have been proposed to prevent asthma by enhancing the T H 1-mediated immunity (Strachan 2000).…”
Section: Discussionsupporting
confidence: 91%
“…10,11 Because all of these factors were potential confounders in risk factors analyses, they were controlled as covariates. Although not statically significant, maternal smoking during pregnancy was also a positive predictor of asthma in our population, which was consistent with the finding in a recent report from the Avon Longitudinal Study of Pregnancy and Childhood.…”
Section: E392mentioning
confidence: 99%
“…22,23 These included gender, social class, maternal and paternal asthma, family size, child care use in the first year of life, whooping cough and measles infection, hepatitis B, polio and MMR vaccination, sheepskin use in the first year of life, current use of a waterbed or plastic sheet on the mattress, age of mattress and any current smoking in the house. Sibling asthma, hayfever or eczema were not included in the model because information on maternal and paternal asthma, eczema and hayfever was available to allow for direct control for family history of asthma.…”
Section: Multivariate Analysismentioning
confidence: 99%